Penanaman Mangrove: Aksi Nyata Pelestarian Lingkungan di Peukan Bada Aceh Besar - Gadeng, Ahmad Nubli; Azis, Daska; Desfandi, Mirza; Fitria, Ade; Furqan, Muhammad Hafizul; Ruliani, Ruliani; Zahara, Amelia; Al-Farisi, Muhammad; Ramli, Ramli (LSM Catimore dan Sahabat, 2025)
The mangrove ecosystem plays a vital role in maintaining coastal environmental balance and supporting the socio-economic life of local communities. However, mangrove degradation due to illegal logging, land conversion, and global climate change remains a serious issue in Indonesia. This community service aimed to describe the benefits of mangroves and the implementation of conservation activities through mangrove education and planting in Peukan Bada, Aceh Besar. The method used was descriptive qualitative with literature study and field observation, involving students and lecturers of Geography Education FKIP Syiah Kuala University and local community members. The results showed that education and mangrove planting increased participants’ understanding of the ecological and economic functions of mangroves, fostered environmental awareness, and supported the restoration of degraded coastal ecosystems. This activity also built collaboration between universities and local communities in achieving sustainable mangrove conservation.